2019
DOI: 10.3390/molecules24122273
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Extract of Aerial Parts of Pavetta indica L. Enhances the Cytotoxic Effect of Doxorubicin and Induces Radiation Sensitization in MDA-MB-231 Triple-Negative Breast Cancer Cells

Abstract: Pavetta indica L. is used in traditional medicine for the treatment of various diseases including hemorrhoids, headache, urinary conditions, ulcerated nose, and dropsy. However, no study has evaluated the anticancer effect of P. indica L. In this study, we found that a methanol extract of the leaves and branches of P. indica L. (MEPI) caused cellcycle arrest at the sub-G1 phase and induced apoptosis, as indicated by the activation of caspase-8, -3, -7, and c-PARP. Western blotting revealed that MEPI significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 46 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…A recent study demonstrated the sensitizing effects of lidocaine to cisplatin on human breast cancer lines MCF-7 and MDA-MB-231, a highly aggressive triple-negative breast cancer (TNBC) cell line that exhibits certain MDR properties (Koh et al, 2019;Thi-Kim et al, 2019). As shown in this research, lidocaine (0.01-1 mM), when combined with cisplatin, significantly enhanced the apoptosis ratio and the inhibitory effects of cisplatin on MCF-7 and MDA-MB-231 cells.…”
Section: Lidocaine Sensitizes Cisplatin In Inducing Apoptosis Via Multiple Pathwaysmentioning
confidence: 99%
“…A recent study demonstrated the sensitizing effects of lidocaine to cisplatin on human breast cancer lines MCF-7 and MDA-MB-231, a highly aggressive triple-negative breast cancer (TNBC) cell line that exhibits certain MDR properties (Koh et al, 2019;Thi-Kim et al, 2019). As shown in this research, lidocaine (0.01-1 mM), when combined with cisplatin, significantly enhanced the apoptosis ratio and the inhibitory effects of cisplatin on MCF-7 and MDA-MB-231 cells.…”
Section: Lidocaine Sensitizes Cisplatin In Inducing Apoptosis Via Multiple Pathwaysmentioning
confidence: 99%